Notary Responsibility For Lost Authentic Deeds - Andriawan, Moh. (International Significance of Notary, 2023)
Abstract: An authentic deed is binding evidence which means the truth of the things written in the deed must be recognized by the judge, the deed is regarded as true as long as it is true that no other party can prove otherwise. This deed will be perfect proof in the eyes of the law. The deed received by the parties concerned with the information is usually in the form of a copy, quotation, derivative, or copy of the original deed will be stored in the Repertorium (where the official who issued the deed). So, if there is a problem or problem related to the information written on a deed, then confirmation only needs to be done directly to the place of the official who issued the information legally, there is no type of deed that is fake if it has been issued by an official authorized by the state. So what happens if a notary in carrying out a position finds the loss of an authentic deed that should be stored properly and correctly, outside of the occurrence of force majeure due to natural disasters, because the notary at the time of carrying out his position must be guided by  Article 16 paragraph (1) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary ("Law 2/2014")  which must be obeyed and obeyed by the notary at the time of appointment and office from the date of appointment as a notary and until the retirement of the notary position he holds, because the Authentic Deed is a state document and is hereditary.Keywords: Notary, Responsibility, Authentic Deed